Subtract and simp \( 6 \frac{3}{10}-2 \frac{2}{5} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
First, let’s convert the mixed numbers into improper fractions. For \( 6 \frac{3}{10} \), we have \( 6 \times 10 + 3 = 60 + 3 = 63 \), so it becomes \( \frac{63}{10} \). For \( 2 \frac{2}{5} \), we have \( 2 \times 5 + 2 = 10 + 2 = 12 \), which makes it \( \frac{12}{5} \). Next, we need a common denominator to subtract these fractions. The least common multiple of 10 and 5 is 10. Thus, we convert \( \frac{12}{5} \) into \( \frac{24}{10} \). Now, we can subtract: \[ \frac{63}{10} - \frac{24}{10} = \frac{63 - 24}{10} = \frac{39}{10} \] To simplify, we can convert back to a mixed number: \[ \frac{39}{10} = 3 \frac{9}{10} \] So, \( 6 \frac{3}{10} - 2 \frac{2}{5} = 3 \frac{9}{10} \).